2013
DOI: 10.1152/ajpheart.00594.2012
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the Na,K-ATPase α2-isoform in cardiac myocytes delays pressure overload-induced cardiac dysfunction

Abstract: The α2-isoform of the Na,K-ATPase (α2) is the minor isoform of the Na,K-ATPase expressed in the cardiovascular system and is thought to play a critical role in the regulation of cardiovascular hemodynamics. However, the organ system/cell type expressing α2 that is required for this regulation has not been fully defined. The present study uses a heart-specific knockout of α2 to further define the tissue-specific role of α2 in the regulation of cardiovascular hemodynamics. To accomplish this, we developed a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…However, two landmark, but underappreciated, articles published in this journal, and a more recent report in Circulation Research, in which transaortic constriction (TAC), a common model, was used to induce pressure overload, have demonstrated that this view is not entirely correct. Notably, experiments on mice with genetically engi-neered cardiac ␣ 2 -Na ϩ pumps can exhibit substantial TACinduced elevation of LV systolic pressure (LVSP) but greatly attenuated cardiac hypertrophy and dysfunction (15,82,112). Those observations, which are summarized here, provide the basis for a new explanation for how pressure overload triggers the cardiac structural and functional changes that characterize hypertrophy ( Figs.…”
mentioning
confidence: 81%
“…However, two landmark, but underappreciated, articles published in this journal, and a more recent report in Circulation Research, in which transaortic constriction (TAC), a common model, was used to induce pressure overload, have demonstrated that this view is not entirely correct. Notably, experiments on mice with genetically engi-neered cardiac ␣ 2 -Na ϩ pumps can exhibit substantial TACinduced elevation of LV systolic pressure (LVSP) but greatly attenuated cardiac hypertrophy and dysfunction (15,82,112). Those observations, which are summarized here, provide the basis for a new explanation for how pressure overload triggers the cardiac structural and functional changes that characterize hypertrophy ( Figs.…”
mentioning
confidence: 81%
“…Peripheral vascular resistance is defined as the ratio of mean blood pressure (mmHg) to blood flow rate (μl min −1 ) (Rindler et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The tail-cuff measurements were also done in anaesthetized mice. Peripheral vascular resistance is defined as the ratio of mean blood pressure (mmHg) to blood flow rate (μl min −1 ) (Rindler et al 2011).…”
Section: No Measurementsmentioning
confidence: 99%
“…increased end‐diastolic and systolic volumes, and decreased ejection fraction (EF) (Rindler et al . ). However, cardio‐specific α2, but not α1, overexpression also attenuates TAC‐induced HH (Correll et al .…”
Section: Introductionmentioning
confidence: 97%
“…These considerations also explain why both cardiac‐α2 knockout (Rindler et al . ) and overexpression (Correll et al . ) delay/attenuate TAC‐induced cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%